Motorized Cover Lifter Provides Mobile Access to Manholes. Issue 9 (1st September 2013) - Ouellet, Jean‐Marc; Savage, Yvan
Abstract : The Motorized Manhole Cover Lifter, a motorized, self‐supporting unit made of recycled and wheelchair parts, was created for lifting manhole covers.